Pemanfaatan Digital Marketing oleh Pelaku UMKM di Kuningan Barat Jakarta Selatan - Radja Erland Hamzah; Citra Eka Putri (Jurnal Pustaka Dianmas, 2021)
Social media has the potential to help SMEs in marketing their products. The presence of various online (digital) shopping platforms is a potential market for anyone, especially UKMK players to get involved so that they can optimally enter the digital world. Almost all of these platforms are based on the internet, even social media, which is currently almost used by the Indonesian people, is used to sell or market products, services and services. Utilization of digital marketing for MSME actors through training in stages, first: research conducted in the Kuningan Barat Village, South Jakarta, second: Socialization through collaboration with Kuningan Barat Village, and third: Creating a digital marketing training schedule by forming groups divided into 4 sessions. To carry out this socialization, lecture and discussion methods and practice were used. The socialization was carried out to provide an understanding of digital concepts, social media and the benefits of using social media. Assistance in digital marketing management, both in finance and business management. In addition, assistance is also carried out to improve technical capabilities for content: WhatsApp Business, Instagram and Facebook, Website www.plazakuninganbarat.com is one of the outputs of this activity, namely a website in the form of a mini marketplace that can be used as a display store as well as a marketing medium for MSMEs native to Kuningan. West.